Analisa Penanganan Banjir Genangan di Permukiman Villa Buana Kabupaten Aceh Besar - Adamy, Ghazali; Syahputra, Ichsan; Zardi, Muhammad (Jurnal Teknik Sipil Unaya, 2025)
Villa Buana is a settlement located in Dusun Ujung Engking, Darul Imarah District, Aceh Besar Regency. The flood that occurred in 2020 resulted in the overflow of drainage channels by 50-100 cm. This study aims to analyze the handling of standing floodwaters based on rainfall calculations using a return period of 2 years and planned discharge calculations using the rational method and HEC-RAS 4.0 simulation modeling.The working concept of this drainage system plan is that rainwater runoff entering the residential drainage is channeled to the planned drainage through three levels of conveyance: network channels, secondary channels, and main channels, leading to the output or existing drainage.Based on the re-evaluations conducted every two years using the Log Pearson Type III method, a standard deviation (Sd) of 0.1219 was obtained, a skewness coefficient (Cs) of 2.838, and a rain intensity calculation of 35.59 mm/hour. The discharge calculation using the rational method yielded a discharge of 0.786 m³/second. This planned drainage system consists of 16 segments, including 7 main channels, 2 secondary channels, and 7 network channels.